National Sentiment and Economic Behavior: Evidence From Online Betting on European Football - Sebastian Braun; Michael Kvasnicka (Journal of Sports Economics, 2013)
National sentiment can have major implications for individual consumption and investment choices but has been researched little by economists. This article studies how national sentiment in the form of a perception or loyalty bias of bettors may affect pricing patterns on national wagering markets for European football. The authors show theoretically that both biases can be profitably exploited by domestic bookmakers through price adjustment. Analyzing empirically a unique data set of betting odds from online bookmakers in Europe, the authors find evidence of systematic biases in the pricing of own national teams, deviations that can be explained by the aforementioned two biases.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; national sentiment; betting markets; home bias; investment